2000
DOI: 10.1097/00006454-200011000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Immunization against hepatitis A in the first year of life: priming despite the presence of maternal antibody

Abstract: Our results suggest that the initially seropositive infants were primed despite maternal antibody interference. The hepatitis A vaccine was well-tolerated in this population of young infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(71 citation statements)
references
References 18 publications
5
62
0
3
Order By: Relevance
“…The B-cell immune responses of infants were inhibited in the presence of MatAbs until the MatAb titer had fallen below a specific threshold. However, the infants' responses showed that they had been primed by the initial vaccination despite the interference, indicating unaffected T-cell priming (10). Based on our results, it is conceivable that in the presence of the high MatAb levels, the Pnc1-TT-immunized offspring might respond to a booster dose of Pnc1-TT when the MatAbs have fallen below a critical threshold.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The B-cell immune responses of infants were inhibited in the presence of MatAbs until the MatAb titer had fallen below a specific threshold. However, the infants' responses showed that they had been primed by the initial vaccination despite the interference, indicating unaffected T-cell priming (10). Based on our results, it is conceivable that in the presence of the high MatAb levels, the Pnc1-TT-immunized offspring might respond to a booster dose of Pnc1-TT when the MatAbs have fallen below a critical threshold.…”
Section: Discussionmentioning
confidence: 68%
“…Student's t test and nonparametric test (Mann-Whitney) were used to compare log antibody titers and numbers of CFU (log 10 …”
Section: Methodsmentioning
confidence: 99%
“…A study conducted in India presented data suggesting that children should be immunized against HAV by 10 months of age, when the maternal antibodies disappear (Chadha et al 1999). Pre-existing maternal antibodies do interfere with the immune response to hepatitis A vaccine (Dagan et al 2000, Letson et al 2004, although some studies have shown that infants born to anti-HAV-positive mothers develop anamnestic responses with a booster dose of hepatitis A vaccine (Fiore et al 2003, Letson et al 2004.…”
Section: Discussionmentioning
confidence: 99%
“…No obstante, el 85 a 95% de los adultos inmunocompetentes seronegativos (75 a 80% en personas sobre 40 años) que reciben la primera dosis de vacuna, presentan anticuerpos anti VHA en el plazo de 10 a 14 días, sobre los niveles protectores 5-8 ; a los 28 días cerca del 100% alcanzó títulos protectores, y en una concentración superior a la primera determinación [5][6][7][8] . Esta respuesta es similar en niños de toda edad [9][10][11][12] , con títulos algo menores si la vacuna es administrada en el primer año de vida [13][14][15][16][17][18] . En estudios comparativos se ha observado mayores títulos de anticuerpos otorgados por algunas vacunas que otras, lo que no parece tener mayor relevancia en el corto ni a largo plazo pues se trata de diferencia entre concentraciones que son siempre 10 a 100 veces superiores a las protectoras.…”
Section: Inmunogenicidadunclassified
“…Sin embargo, estudios de inmunogenicidad posteriores efectuados en lactantes en su segundo año de vida con Avaxim 80® UI y Havrix® 720 UE 34,35 , comprobaron que ya a esa edad la inmunidad materna no interfiere sobre la frecuencia ni la intensidad de la respuesta inmune específica y, considerando estos nuevos antecedentes, se autorizó la licencia en Europa y algunos países latinoamericanos, a partir de los 12 meses de edad. Bajo un año de vida, la transferencia pasiva de anticuerpos anti VHA sí interfirió parcialmente esta respuesta a vacuna Havrix® 720 UE 15 , Havrix® 360 UE 13,14 y Avaxim® 80 UI [16][17][18] observándose menores títulos de anticuerpos anti VHA en hijos de mujeres seropositivas que en hijos de mujeres seronegativas, aunque la seropositividad de la madre no impidió la estimulación inmune y priming en el lactante por el antígeno vaccinal 15,16 . una notable y rápida reducción de la incidencia de la enfermedad en 3 años, no sólo en las cohortes vacunadas sino que a toda edad 36,37 .…”
Section: Inmunogenicidadunclassified